Evidence of a Dose-Rate Threshold for Life Span Reduction of Dogs Exposed Lifelong to γ-Radiation - Jerry M. Cuttler; Ludwig E. Feinendegen; Yehoshua Socol (SAGE Publishing, 2018)
Our return to a study on dogs exposed lifelong to cobalt-60 γ-radiation was prompted by a comment that data in dog studies have large statistical errors due to the small number of dogs. We located an earlier article on the same study that had a better mortality curve for the dogs in each dose-rate group. The median life span of the dogs in each group was tabulated, and the standard error of each was calculated. No statistically significant shortening of median life span was observed for the lowest dose-rate group at any reasonable significance level ( P value: .005-.05), whereas for dogs with higher irradiation rates, life span shortening was statistically significant at highest reasonable significance level ( P value: .005). The results were entered on a graph of life span versus dose rate, assuming a threshold dose-response model. The fitted line indicates that the dose-rate threshold for γ-radiation induced life span reduction is about 600 mGy per year, which is close to the value we found previously. Making allowance for the calculated standard errors, we conclude that this threshold is in the range from 300 to 1100 mGy per year. This evidence is relevant for emergency measures actions (evacuation of residents) and for nuclear waste management.